(Benzoato-κ(2) O,O′)(5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane-κ(4) N,N′,N′′,N′′′)nickel(II) perchlorate monohydrate - Ou, Guang-Chuan (International Union of Crystallography, 2008)
The Ni atom in the title salt, [Ni(C(7)H(5)O(2))(C(16)H(36)N(4))]ClO(4)·H(2)O, is in a six-coordinate octahedral geometry. The metal atom is chelated by the carboxylate group, and the macrocyclic ligand adopts a folded configuration. The cation, anion and water molecules engage in hydrogen bonding to form a layer structure.